PEMILIHAN MODEL PERABOT PADA RUANG DALAM RUMAH TINGGAL SEDERHANA (STUDI KASUS RUMAH TYPE 36, 45, 54) - Trumansyahjaya, Kalih (Universitas Bina Taruna Gorontalo, 2015)
ABSTRAK A good desainer interior have to involve the space facility to be created, he/she have to can feel the sliceof space, how many minimum requirement have to be reserved for a freedom of move, the traffic, service. First phase, determined of zone for the type of activity to be happened in the space, then reckoned a space requirement from one who will take possession of, because space requirement each differing one another, depended of whom one who will take possession. It is evaluated from education facet, position, experience, etcetera. Therefore in arranging dinky house non easy work. Space limitation become the constraint important is how to make the space in an optimal fashion, and how house have to be balmy fixed taken possession of and can accomodate all activity of the ownerr. Others also how house have to be delicate looked into, non simply place shelter the. Optimal settlement cannot broaden the space. But, arrangedly well, space limited do not become unrelax or narrow, broader and satisfy. Key words : Space Requirement, Interior, Dinky House